(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article presents the results of a study on the determination of the peroxidase enzyme weakly bound to the cell membrane and soluble form in Datura stramonium L. plants mechanically inoculated with PTV. Soluble peroxidase produced 46.92±0.49* in the leaves of infected plants in the 1st week, 82.07±0.43 in healthy leaves, and peroxidase weakly bound to the cell membrane produced 46.88±0.46 in healthy leaves, 88.8±0.34* in infected leaves, and other values are fully reflected in the article. At the same time, the results of the dynamics of changes in enzyme activity under the influence of viruses over 3 weeks are described, and this indicator was determined every week.